Factor Affecting Work Life Balance of married Working Women in Nepal Sbi Bank Ltd - Acharya, Paras Mani (Damak Campus Journal, 2023)
This study attempted to examine the relationship between the perceived work life balance of working women and the affecting factors like support system, dependent care and working hours in the banks. The study also focused on identifying the impact of different demographic variables like age, income level, parental status, family size on the relationship between the chosen dependent and independent variables. The study was conducted within branches of Nepal SBI Bank Ltd and the target population is the set of all married female staffs working for NSBL.